Analyzing the manifestations of conflict in the Algerian organizations through some empirical studies - gherraz, taher; botouten, mohamed saleh (Journal of Social Sciences and Humanities, 2021)
We aim behind this article to analyze the most important empirical studies conducted in a number of institutions and societies that differ or coincide in some of their manifestations with the reality of the Algerian institution, as all of them sought to track labor relations through interactions between workers and employers or between representatives Workers such as trade unions and the administration, all in order to achieve labor demands on the part of the working class, or in order to extend the influence and control of the matter by the administration, including avoiding conflict situations represented in labor strikes, absences, sabotage operations, work stoppages, and the increase Complaints and grievances, and an attempt to contain them. The study concluded that there are multiple forms and manifestations of labor conflicts, and this is what led researchers to try to understand the phenomenon of conflict in the institution in its concomitant relationship with society alike.